Konsep Ngayah Berbasis Tri Hita Karana dalam Instalasi Lampu Penerangan Panel Surya di Pura Padharman - Suputra Widharma, I Gede; Kiriana, I Nyoman; Putri, I Dewa Ayu Hendrawathy (Sevanam: Jurnal Pengabdian Masyarakat, 2026)
The Tri Hita Karana-based ngayah concept in community service activities involves installing solar-powered lighting at Padharman Temple. This community service involves installing solar-powered lighting in the temple's parking area. This lighting installation is necessary because the parking area is often poorly lit at night. The use of solar panels as a power source is ideal for the parking area, which is free of trees and quite far from the electricity grid. The solar-powered lighting installation was assisted by students, temple caretakers, and the local community. In addition to increasing solar-powered lighting in the parking area, the ngayah activity also provided guidance on how to use solar panel technology. Increasing the lighting intensity in the parking area allows for smooth and environmentally friendly nighttime activities. It also aims to increase public understanding of the technical instructions for installing and maintaining solar-powered lighting. This Tri Hita Karana-based ngayah concept has succeeded in providing services and increasing local community insight into solar panels and their use.